2015
DOI: 10.3389/fnhum.2015.00376
|View full text |Cite
|
Sign up to set email alerts
|

Self-esteem modulates automatic attentional responses to self-relevant stimuli: evidence from event-related brain potentials

Abstract: Previous studies have widely shown that self-esteem modulates the attention bias towards social rejection or emotion-related information. However, little is known about the influences of self-esteem on attention bias towards self-relevant stimuli. We aimed to investigate neural correlates that underlie the modulation effect of self-esteem on self-relevant processing. Event-related potentials (ERP) were recorded for subjects' own names and close others' names (the names of their friends) while subjects performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 53 publications
1
18
0
Order By: Relevance
“…More specifically, highly salient stimuli such as negative emotional stimuli usually elicited larger P2 amplitudes than positive or neutral emotional stimuli (Carretié et al, 2001(Carretié et al, , 2004. It has been also found that self-name elicited larger P2 amplitudes than other names (Chen, Shui & Zhong, 2015;Chen et al, 2011). Consistent with previous studies, the present study also observed larger P2 amplitudes in self-condition (individual self) compared with the famous person-condition.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…More specifically, highly salient stimuli such as negative emotional stimuli usually elicited larger P2 amplitudes than positive or neutral emotional stimuli (Carretié et al, 2001(Carretié et al, , 2004. It has been also found that self-name elicited larger P2 amplitudes than other names (Chen, Shui & Zhong, 2015;Chen et al, 2011). Consistent with previous studies, the present study also observed larger P2 amplitudes in self-condition (individual self) compared with the famous person-condition.…”
Section: Discussionsupporting
confidence: 91%
“…More recently, event-related potentials, a high-temporal resolution technique recording neural activity with millisecond precision, have been widely used to investigate the time course of self-referential processing and its neural correlates. For example, electrophysiological studies found an obvious self-relevant effect on the early P2 component, which is a positive component peaking at the latency of around 200 ms after stimulus onset (Chen, Shui & Zhong, 2015;Liu et al, 2019). In addition, self-relevant effect could also occur on the N2 component, a negative deflection peaking between 200 and 350 ms after stimulus onset, with smaller N2 amplitudes induced by participants' own than by other faces or handwritings (Chen et al, 2008;Keyes et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Early self-related identification is usually found in Chinese populations for both explicit (Sui et al, 2012c ; Zhang et al, 2013 ) and implicit (Sui et al, 2009 ; Fan et al, 2011 , 2013 ; Yang et al, 2012 ; Liu et al, 2016 ) self-referential processing. There is even a temporal sensitivity to the self-relevant degree effect in Chinese individuals (Chen et al, 2011 , 2015 ; Guan et al, 2014 ). Our finding of early self-discrimination is consistent with studies of Chinese subjects (Sui et al, 2009 , 2012c ; Chen et al, 2011 , 2015 ; Fan et al, 2011 , 2013 ; Yang et al, 2012 ; Zhang et al, 2013 ; Guan et al, 2014 ; Liu et al, 2016 ) and Western populations (Herbert et al, 2011a ; Sui et al, 2012c ; Tacikowski et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The widely reported self-prioritization effect in perception and memory suggests a social discrimination function of self (Macrae et al, 2004 , 2017 ; Sui et al, 2012a , b , 2015 ; Schäfer et al, 2015 , 2016 ). The components of N1 (50–150 ms), P2 (about 150–250 ms), and P300 (about 300–500 ms) have shown the advantage effect for self-relevant stimuli (Zhao et al, 2009 , 2011 ; Fan et al, 2011 ; Yang et al, 2012 ; Chen et al, 2015 ; Liu et al, 2016 ). Interestingly, self-identification is highly sensitive to temporal processing, and there is a self-relevant degree effect where high self-relevant stimuli are preferentially processed relative to those low in self-relevance (Chen et al, 2011 , 2015 ; Guan et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation